METHODOLOGICAL BASIS OF FORMING PHILOSOPHICAL THINKING IN STUDENTS BASED ON ARTIFICIAL INTELLIGENCE - Nodirbekov Furqatbek Umarjon oglu (Modern American Journals, 2025)
This article examines the methodological foundations of applying artificial intelligence technologies in developing students’ philosophical knowledge. In modern education, philosophical thinking is shaped not only through theoretical studies but also by integrating digital tools. Artificial intelligence supports students in conducting independent research, improving logical and critical reasoning, and analyzing philosophical issues on a broader scale. The paper emphasizes methodological approaches that enhance philosophy teaching through AI and demonstrates its importance in increasing educational quality, fostering deeper understanding, and adapting philosophy education to the needs of the digital era.